Location based service for the mobile users using the GPS technology - Rahman, Mir Sazzadur; Haque, SM. Hasan Hafizul (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2012.